Canadian foreign policy in Africa regional approaches to peace, security, and development - Akuffo, Edward Ansah (Global security in a changing world, 2012)
For the first time, Edward Akuffo combines historical and contemporary material on Canada's development and security policy while analysing the linkage between these sets of foreign policy practices on the African continent. The book makes an important contribution to the debate on Canada's foreign policy generally, and on Africa's approach to peace, security and development, while shedding light on a new theoretical lens - non-imperial internationalism - to understand Canada's foreign policy.